The Effect of Emotional Intelligence, Self-efficacy, and Team Cohesion on the Performance of Teachers at Serang Regency Private Elementary School - Ade Lusiyana Nur Octavia Illahi; Bambang Dwi Suseno; Udin Suadina (Universitas Mercu Buana, 2023)
Objectives: Teachers need to know a lot about their subjects, be good at creating, managing, and evaluating learning using a variety of new methods, and be good at using teaching aids and learning media. They also need to be mature and require a tough personality. Therefore, the objective of this research was to discover whether or not emotional intelligence and self-efficacy affected the performance of educators in either a direct manner or in a more indirect manner through team cohesion.Methodology: The method is a quantitative research using a correlational approach. The population of this study was private elementary school teachers in Serang Regency with as many as 405 people and a sample of 140 respondents. Data was analyzed through Partial Least Squares-Structural Equation Model (PLS-SEM) using SmartPLS 3.2.7 software.Finding: Emotional intelligence and self-efficacy were found to affect the performance of educators and both affected team cohesion. Team cohesion was also found to affect educator performance and was able to mediate between the influence of emotional intelligence and self-efficacy on educator performance.Conclusion: To improve the performance of educators, emotional intelligence and self-efficacy needs to be improved, as well as team cohesion.